Cation-activated Nucleotidase in Cell Envelopes of a Marine Bacterium - Thompson, J. (1969)
Isolated cell envelopes of a marine bacterium, M.B.3, have been prepared which possess a nonspecific, cation-activated nucleotidase. The cell envelope comprises approximately 35% (dry weight) of the whole cell and contains protein, 60.2%; lipids, 20.7%; hexose, 3.4%; and ribonucleic acid, 4.6%. No deoxyribonucleic acid could be detected in the preparations. The nucleotidase has an essential requirement for Mg(2+); maximum activation at pH 8.0 occurs at a divalent cation concentration of approximately 80 mm. At a Mg(2+) to adenosine 5′-triphosphate (ATP) ratio of 2:1, the enzyme was further stimulated by monovalent cations Na(+), K(+), NH(4)(+), and Li(+). Maximum activity was found at a monovalent ion concentration of approximately 0.3 m. The envelope preparation liberated inorganic orthophosphate (P(i)) from ATP, adenosine 5′-diphosphate (ADP), and adenosine 5′-monophosphate (AMP) at similar rates. Thin-layer and ion-exchange chromatography show that when AMP, ADP, and ATP were utilized as substrate, approximately 1, 2, and 3 moles of P(i), respectively, were produced per mole of adenosine. P(i) was also liberated from the 5′-triphosphates of guanosine, uridine, and cytidine. The enzyme preparation did not attack p-nitrophenyl phosphate, β-glycerophosphate, or inorganic pyrophosphate. Sulfhydryl inhibitors p-chloromercuribenzoate, N-ethyl maleimide, and iodoacetate had little effect upon the nucleotidase activity. Ca(2+) and ethylenediaminetetraacetic acid caused complete inhibition of the system, whereas ouabain had no effect upon the enzyme activity. The concentrations of Na(+) (0.3 m) and Mg(2+) ions (60 to 80 mm) required for maximum ATP-hydrolyzing activity were similar to those concentrations necessary for maintenance of cell integrity and for the prevention of cell lysis.